1976
DOI: 10.1111/j.1365-2362.1976.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Meal Feeding and of Sham‐Feeding on Insulin Secretion in Dogs

Abstract: After feeding intact conscious dogs 1000 g mashed meat, peripheral venous immunoreactive insulin activity (IRI) increases before any enhancement of amino nitrogen concentration. This course of IRI is paralleled by a decrease of free fatty acids. Meal feeding in dogs, whose pancreatic juice is completely diverted from the gut by a fistula, is followed by a similar IRI increase without a distinct enhancement of amino nitrogen. In oesophagus fistula dogs, sham-feeding meat in 9 out of 15 experiments results in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Alternatively, as discussed below, differential responses in cephalic phase insulin and pancreatic polypeptide release suggest that factors other than vagal activation may modulate CPIR. Cephalic phase glucagon release, although documented in rats and dogs (Fischer et al, 1976), has only recently been shown in humans. In a study conducted by Secchi et al (1995), control subjects and recipients of pancreas-kidney transplants ingested a palatable meal while blood was sampled rapidly for a 10 min period.…”
Section: Innervation Of the Endocrine Pancreas Innervation Of The Endmentioning
confidence: 98%
“…Alternatively, as discussed below, differential responses in cephalic phase insulin and pancreatic polypeptide release suggest that factors other than vagal activation may modulate CPIR. Cephalic phase glucagon release, although documented in rats and dogs (Fischer et al, 1976), has only recently been shown in humans. In a study conducted by Secchi et al (1995), control subjects and recipients of pancreas-kidney transplants ingested a palatable meal while blood was sampled rapidly for a 10 min period.…”
Section: Innervation Of the Endocrine Pancreas Innervation Of The Endmentioning
confidence: 98%
“…The "cephalic phase" of food ingestion has been known to be potent to induce gastrointestinal physiological responses (saliva secretion) since Pavlov [46], and "sham feeding" techniques have been used in humans to induce gastric emptying [47], gastric acid [48] and pancreatic secretion [49,50], insulin [51] and Immunoglobulin A release [52]. Although Wolf and Wolf [53] previously described an increase in gastric motor activity when food was discussed with a fistulated patient, only limited attention has been given to cephalic influences on gastric motor activity.…”
Section: Discussionmentioning
confidence: 99%
“…We (Woods et al, 1977) and others (see reviews in Teff, 2000 andStrubbe andWoods, 2004) have found that environmental stimuli that predict when food will become available, including the time of day, elicit cephalic insulin secretion at that time even if no meal is forthcoming. Importantly, in addition to insulin, many other hormones and enzymes that aid the digestion and absorption processes are also secreted cephalically in anticipation of meals, including ghrelin (Drazen et al, 2006), glucagon-like peptide 1 (GLP-1) (Vahl et al, 2010), pancreatic polypeptide (Floyd et al, 1976;Teff, 2010), and glucagon (Fischer et al, 1976;Secchi et al, 1995), as well as meal-related neuropeptides such as hypothalamic NPY (Yoshihara et al, 1996a(Yoshihara et al, , 1996b. Cephalic secretion of so many meal-related metabolic compounds represents regulation at its best.…”
Section: Mechanisms Of Physiological Regulation: Importance Of Learningmentioning
confidence: 99%